Zoonotic enteric parasites in Mongolian people, animals, and the environment: Using One Health to address shared pathogens. - Amber N Barnes; Anu Davaasuren; Uyanga Baasandavga; Paul M Lantos; Battsetseg Gonchigoo; Gregory C Gray (Public Library of Science (PLoS), 2021)
Background Cryptosporidium spp. and Giardia duodenalis are important zoonotic enteric pathogens of One Health concern for humans, animals, and the environment. For this study, we investigated parasite prevalence and risk factors among rural, peri-urban, and urban households and environments of Mongolia. Methods This cross-sectional study implemented a household risk factor survey at 250 home sites along with sample collection from humans, animals, flies, and drinking water. Multiplex real-time PCR analysis was conducted to look for Cryptosporidium spp. and/or Giardia duodenalis within household samples. Results Lab analysis found one or both zoonotic parasites at 20% of the participating households (51/250). Human samples had a parasite prevalence of 6.4% (27/419), domestic animals at 3.3% (19/570), pooled filth flies at 14.8% (17/115), and drinking water samples at 2% (5/250). Parasite presence at the household was significantly associated with a household's use of an improved drinking water source (OR 0.27; CI 0.12-0.61; p = < 0.01), having an indoor handwashing site (OR 0.41; CI 0.19-0.92; p = 0.03), domestic animal ownership (OR 2.40; CI 1.02-5.65; p = 0.05), and rural location (OR 0.50; CI 0.25-0.98; p = 0.04). Household use of an improved drinking water source remained significant in the multivariate model (OR 0.16; CI 0.04-0.68; p = 0.01). Conclusion In Mongolia, public and veterinary health are intertwined, particularly for rural herding households. Increased access to safe water, sanitation and hygiene infrastructure could help prevent further transmission of zoonotic enteric parasites. Public health interventions, policy and messaging should utilize a One Health framework employing joint leadership from local human and animal health sectors.